Arresting Images: Mug Shots from the OPP Museum. PETERBOROUGH MUSEUM & ARCHIVES - Aoki, Jodi (Archivaria, 2017)
Arresting Images: Mug Shots from the OPP Museum. PETERBOROUGH MUSEUM & ARCHIVES, PETERBOROUGH, ONTARIO 17 December 2016–19 March 2017. Curated by KIM REID.